Indoctrination and Education: Considerations From the Radical and Inclusive Approach for Teaching - de la Herrán-Gascón, Agustín (2024)
Introduction. Indoctrination is currently a widely debated topic in social and educational theory, with discussions about its definition, causes, relationship with education, and alternatives. This paper analyzes indoctrination from the point of view of the radical and inclusive approach developed by the authors thirty years ago, incorporating classical Eastern perspectives and concepts into pedagogy and education. Aims. The objectives of the study are to examine the relationships between egocentrism, learning, and indoctrination and to outline a consciousness-based educational alternative from the radical and inclusive approach to education. Discussion. A dialectical pedagogical essay analyzes indoctrination from human egocentrism and current education based on learning, disciplinary knowledge, and competencies. As an alternative, the paper proposes an education based on consciousness, which includes processes of deconditioning and educational evolution from ego to consciousness. Conclusions. Indoctrination is the opposite of education. The primary challenge in educational teaching is determining whether to indoctrinate or educate. Education based on learning and competencies can be compatible with indoctrination. Egocentric systems (national, religious, ideological, military, scientific, cultural, educational, or other) can be sources of indoctrination. The most relevant didactic criterion is whether conscious educational institutions and educators conduct teaching. These conclusions have broad implications for the initial and in-service training of teachers and other educators, whether at personal or systemic levels.